A Computational and Experimental Study of Thieno[3, 4‐b]thiophene as a Proaromatic π‐Bridge in Dye‐Sensitized Solar Cells. Issue 2 (2nd December 2015) - Brogdon, Phillip; Giordano, Fabrizio; Puneky, George A.; Dass, Amala; Zakeeruddin, Shaik M.; Nazeeruddin, Mohammad Khaja; Grätzel, Michael; Tschumper, Gregory S.; Delcamp, Jared H.
Abstract: FourD ‐π‐A dyes (D=donor, A=accpetor) based on a 3, 4‐thienothiophene π‐bridge were synthesized for use in dye‐sensitized solar cells (DSCs). The proaromatic building block 3, 4‐thienothiophene is incorporated to stabilize dye excited‐state oxidation potentials. This lowering of the excited‐state energy levels allows for deeper absorption into the NIR region with relatively low molecular weight dyes. The influence of proaromatic functionality is probed through a computational analysis of optimized bond lengths and nucleus independent chemical shifts (NICS) for both the ground‐ and excited‐ states. To avoid a necessary lowering of the TiO2 semiconductor conduction band (CB) to promote efficient dye–TiO2 electron injection, strong donor functionalities based on triaryl‐ and diarylamines are employed in the dye designs to raise both the ground‐ and excited‐state oxidation potentials of the dyes. Solubility, aggregation, and TiO2 surface protection are addressed by examining an ethylhexyl alkyl chain in comparison to a simple ethyl chain on the 3, 4‐thienothiophene bridge. Power conversion efficiencies of up to 7.8 % are observed. Abstract : Vote proaromatic! Four D‐π‐A dyes (D=donor, A=accpetor) based on a 3, 4‐thienothiophene bridge have been synthesized, analysed computationally and evaluated in dye‐sensitized solar cell devices. The proaromatic nature of the 3, 4‐TT bridge is supported through computational analysis and devices showing performances nearing 8 % power conversion efficiency for these concise dyes.